19.5: Reconfigurable microfluidic interface programmed by conductive‐microstructure induced localized instability. (17th October 2022) - Feng, Hao; Lin, Tao; Guo, YuanYuan; Tang, Biao; Zhou, Guofu
Abstract : Electrofulidic displays is a reflective display technology based on the principle of electrowetting for high‐speed operation of liquid interface. For this, precise control of the relative motion of the two‐phase fluid is very important for optical performance. However, due to the instability of the liquid‐liquid interface under an electric field, it is very difficult to accurately control the relative dynamics of the two‐phase fluid through electrowetting. Therefore, how to realize the stable and controllable dynamics of the oil‐water interface is an interesting challenge. At present, there have been many researches aimed at this problem in terms of device structure [1], electrode design [2], driving waveform [3], etc.However, due to the characteristics of the material or the limitation of the structure manufacturing process, these methods still cannot form a stable control of the movement of the oil‐water interface. In this paper, through the flexible programmable inkjet printing process, conductive micropiller (CMP) are implanted in the pixel structure to induce local distortion electric fields to further precisely control the movement of the oil‐water two‐phase interface.